Tuning into urban birdsong: enhancing nature connectedness with an AI-powered wearable - Zhuying Li; Si Cheng; Xiaoqing Sun; Xipei Ren; Yan Wang; Min-Ling Zhang (Scientific Reports)
Abstract The rapid urbanization has led to the loss of natural spaces and a subsequent disconnection between humans and nature, negatively affecting residents’ well-being and environmental awareness. There is a a growing interest in leveraging technology to address this gap in Human-Computer Interaction. This article introduces GoChirp, an AI-powered wearable device for enhancing nature relatedness within urban landscapes. By utilizing machine learning algorithms, GoChirp recognizes bird sounds in the environment and provides haptic feedback that mimics the bird flapping, directing users’ attention to avian life and fostering a heightened awareness and connection to nature. To evaluate GoChirp, we conducted a week-long field study with 36 urban participants divided into two groups: an experimental group using GoChirp and a control group using a dummy device. We used pre- and post-study questionnaires to assess changes in participants’ nature relatedness. Additional questionnaires and semi-structured interviews were employed to evaluate the device’s usability and user experience. The results suggest that AI-powered wearables like GoChirp, have the potential to augment individual’s sensory and cognitive capabilities, enabling a deeper connection with the natural environment. This could further enhance users’ well-being and potentially foster a greater sense of responsibility towards the natural environment, leading to mutual benefits between humans and nature.